1998
DOI: 10.1103/physrevb.57.2536
|View full text |Cite
|
Sign up to set email alerts
|

Electronic structure of nitrogen-carbon alloys(aCNx)determined by photoelectron spectroscopy

Abstract: The electronic structure of nitrogen-containing diamondlike films prepared by sputtering was determined by photoelectron spectroscopy. The N 1s core-level spectra are constituted by two peaks at 400.5 and 398.2 eV associated with substitutional N sp 2 in aromatic rings and N bonded to C sp 3 , respectively. On increasing N, the top of the valence band suffers profound changes. The new features are identified by a comparison of the experimental spectra with theoretically calculated density of states of nitrogen… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

21
149
1
1

Year Published

1999
1999
2023
2023

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 237 publications
(172 citation statements)
references
References 19 publications
21
149
1
1
Order By: Relevance
“…These contributions could be attributed to the nitrogenated graphitic clusters (~7 eV and ~10 eV) and nitrogen lone pair states (~5 eV), in good agreement with the work of Souto et al who reported UPS measurements and simulation on nonhydrogenated a-CN x films (nitrogenated graphite clusters and β-C 3 N 4 ). [17] Peaks at ~8 eV and at less than 4 eV could be attributed to carbon σ and π bands, respectively. These peak assignments are consistent with the chemical bonding configurations formed by carbon and nitrogen atoms.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…These contributions could be attributed to the nitrogenated graphitic clusters (~7 eV and ~10 eV) and nitrogen lone pair states (~5 eV), in good agreement with the work of Souto et al who reported UPS measurements and simulation on nonhydrogenated a-CN x films (nitrogenated graphite clusters and β-C 3 N 4 ). [17] Peaks at ~8 eV and at less than 4 eV could be attributed to carbon σ and π bands, respectively. These peak assignments are consistent with the chemical bonding configurations formed by carbon and nitrogen atoms.…”
Section: Discussionmentioning
confidence: 99%
“…[14] Arena et al showed that STM measurements on amorphous carbon nitride also indicate the shoulder of the conduction band becomes steeper when nitrogen is incorporated, which is an effect of n-type doping. [15,16] In addition to the π and σ bands of carbon, the UPS spectra of non-hydrogenated [17] and hydrogenated amorphous carbon nitride [18] (a-CN x , a-CN x :H) exhibit peaks attributed to graphitic C-N and the nitrogen lone pairs, which can be seen in the β-C 3 N 4 like structure. The presence of the N lone pair was also confirmed by direct current-constant photocurrent measurement (dc-CPM) and photoconductivity measurements, assuming the transition from this N lone pair is to the empty π* band.…”
Section: Introductionmentioning
confidence: 99%
“…The components at 398.3 ± 0.2 eV, 399.7 ± 0.2 eV and 400.9 ± 0.2 eV correspond to at least [11,31,35] and to carbon based macromolecular or polymeric substances [47,48]. The current controversy was broadly discussed in [36][37][38][39]49] and is also presented in Fig. 7.…”
Section: Chemical Structurementioning
confidence: 99%
“…The assignment of this peak components to certain bonding states were discussed in a large number of publications based on experimental works devoted to the synthesis of CN x type materials [16][17][18][19][20][21][22][23], N doped graphene [24,25] and nitrogen-containing DLC coatings [8,26,27]. The controversy existing in rendering N-C structures to different chemical shifts was discussed in [16][17][18][19]28]. The determined chemical shifts were assigned in accordance with published data as follows: N1 peak component at 398.3 eV was assigned to C=N-C type chemical bonds, i.e.…”
Section: Chemical Structurementioning
confidence: 99%